2022
DOI: 10.1186/s12877-022-03002-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of having foreign domestic workers on informal caregivers of persons with dementia – findings from a multi-method research in Singapore

Abstract: Background Informal caregivers of persons with dementia (PWDs) sometimes engage foreign domestic workers (FDWs) to support their caregiving journey. However, there has not been much research to establish if this is really beneficial. The current study aims to investigate whether engaging FDWs specifically for caregiving of PWDs truly moderates caregiver stress and to explore caregivers’ experiences of engaging FDWs. Methods A multi-method study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Among the controls, financial adequacy and PCI cognitive function were negatively associated with caregiver strain, whereas caregiver education and spousal caregiver were positively associated with caregiver strain. Hiring FDWs was unrelated to caregiver strain, as the recent study reported [28].…”
Section: Four Profiles Of Care Needsmentioning
confidence: 82%
“…Among the controls, financial adequacy and PCI cognitive function were negatively associated with caregiver strain, whereas caregiver education and spousal caregiver were positively associated with caregiver strain. Hiring FDWs was unrelated to caregiver strain, as the recent study reported [28].…”
Section: Four Profiles Of Care Needsmentioning
confidence: 82%
“…Careers of migrant workers: Migrant workers play an indispensable role in providing home support work, especially in high-income countries ( 271 , 272 ). Female migrant domestic workers globally lack opportunities to develop their career and there is a need for tailored employer responses to support fairness and equality ( 273 276 ).…”
Section: Resultsmentioning
confidence: 99%
“…37 LIMCs presumably play a collaborative caregiving role within the families of individuals with dementia, effectively mitigating depression symptoms and alleviating caregiver stress. 7,12 Families of individuals with Lewy body dementia are more likely to hire LIMCs than families of individuals with other types of dementia. This observation is consistent with previous research findings suggesting that individuals with Lewy body dementia experience difficulties from their substantial behavioral and psychological symptoms, thus resulting in the higher loss of independence and greater functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…These LIMCs provide valuable assistance, which may have positive effects on both the emotional and physical aspects of caregiving. 11–13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation